Chapter EGIPSS model for the evaluation of performance in healthcare - Renzi, Pietro (Proceedings e report, 2021)
The need to improve performance in the Italian healthcare sector and thereby optimise the availability and delivery of related services has long been recognised. The associated reforms and developmental programmes have meant that the focus of health services has moved from a means-based approach to a results-based approach; which was an essential step to enabling real performance improvements according to the new public management paradigm. What is essential is a means of measuring and evaluating changes in healthcare sector performance which will support policy-makers to provide transparency and accountability, in accordance with the Tallinn Charter. This is particularly relevant in the healthcare sector, where outcomes are critical. This paper examines the concept of performance and performance assessment in the healthcare sector; acknowledging the inherent difficulties caused by the complexity of the systems and the multiplicity of performance-related definitions involved. This latter point is illustrated by the fact that many international organisations, such as the WHO and the OECD, have used varying models to assess and compare the performance of health systems in different countries. The authors have compared and evaluated a wide range of models and have determined the merits of the EGIPSS (Évaluation Globale et Intégrée de la Performance des Systèmes de Santé) integrative model. This is based on Parson's theory of social action which specifies four functions necessary for an organisation to survive. EGIPSS takes into consideration the conceptual contributions of different organisations, and covers a comparatively large number of performance measurements. A detailed illustration of the methodology is presented, together with some healthcare-related results for the Republic of San Marino and parts of the Marche Region in Italy.